Book review of: Barcelona: An Urban History of Science and Modernity, 1888-1929. Edited by Oliver Hochadel and Agustí Nieto-Galan. New York: Routledge, 2016 (2016)
How to write histories of science (and technology and medicine)taking into account urban spaces seriously? How the practices ofscience shaped in profound ways modern cities, and, at the sametime, how urban spaces are driving forces for the production andcirculation of scientific knowledge? Of course, these questionsabout the entanglements of science and the city (or about thecoproduction of these two institutions) have attracted increasedattention in the last decades. The so called “spatial turn” in recenthistory of science has helped to place specific city’s sites at thecenter of historical analysis. But for the editors of this extraordinary volume, Oliver Hochadel and Agustí Nieto-Galan, there are stillsome neglected aspects that should be addressed in order to “writea new, genuine urban history of science” (p. 5). A key aspect of this“new” approach is a shift in focus: From metropolis or big cities tosmaller or “second cities”, and from city-based elites or scientificexperts to public or civic science.